Conditional Deletion of EphA4 on Cx3cr1-Expressing Microglia Fails to Influence Histopathological Outcome and Blood Brain Barrier Disruption Following Brain Injury - Soliman, Eman; Mills, Jatia; Ju, Jing; Kaloss, Alexandra M.; Basso, Erwin Kristobal Gudenschwager; Groot, Nathalie; Kelly, Colin; Kowalski, Elizabeth A.; Elhassanny, Mohamed; Chen, Michael; Wang, Xia; Theus, Michelle H. (Frontiers in Molecular Neuroscience, 2021)
Erythropoietin-producing human hepatocellular (Eph) receptors play a major role in central nervous system injury. Preclinical and clinical studies revealed the upregulation of EphA4 receptor in the brain after acute traumatic brain injury. We have previously reported that Cx3cr1-expressing cells in the peri-lesion shows high levels of EphA4 after the induction of controlled cortical impact (CCI) injury in mice. Cx3cr1 is a fractalkine receptor expressed on both resident microglia and peripheral derived macrophages. The current study aimed to determine the role of microglial-specific EphA4 on CCI-induced damage. We used Cx3cr1CreER/+ knock-in/knock-out mice which express EYFP in Cx3cr1-positive cells to establish microglia, EphA4-deficient mice following 1-month tamoxifen injection. Consistent with our previous findings, induction of CCI in wild type (WT) Cx3cr1CreER/+EphA4+/+ mice increased EphA4 expression on EYFP-positive cells in the peri-lesion. To distinguish between peripheral-derived macrophages and resident microglia, we exploited GFP bone marrow-chimeric mice and found that CCI injury increased EphA4 expression in microglia (TMEM119+GFP-) using immunohistochemistry. Using Cx3cr1CreER/+EphA4 f/f (KO) mice, we observed that EphA4 mRNA transcript was undetected in microglia, but remained present in whole blood, when compared to WT. Finally, we found no difference in lesion volume or blood-brain barrier disruption between WT and KO mice at 3dpi. Our data demonstrate a non-essential role of microglial EphA4 on the acute histopathological outcome in response to CCI.